Performance Evaluation of Online Smart Parking System in Jakarta - Suhada, Suhada; Hendriana, Yana (Telematika, 2023)
Purpose: This research aims to evaluate the performance of the Online Smart Parking System application for 7 consecutive days from 06.00 to 18.00 to evaluate the features in the application, evaluate the level of compliance of the clerks with the use of the application and the level of constraints achievement or fulfillment of each of the rights and obligations of the parties, and identification of the level of achievement of revenue targets.Design/methodology/approach: This research was carried out through several stages which include Product Quality Evaluation, Usage Quality Evaluation, Collaboration Evaluation and Financial Evaluation or financial aspects.Findings/result: Design of Logical Framework Application System Online Smart Parking System.Originality/value/state of the art: This research focuses on evaluating the design results of the Online Smart Parking System application which is managed by UP Parking Department of Transportation DKI Jakarta with 3 partner applicators.